Econometric Software - Greene, William (2015)
© 2015 Elsevier Ltd. All rights reserved. This article will describe some of the characteristics of the most widely used econometric software, trace the evolution of this particular type of computer program, and explore the role of computer software in the development of applied econometrics. We begin with a general discussion of econometrics. The specific methodology defined by this field both dictates and is strongly influenced by the software that practitioners use - we return to that issue later in the article. The distinctive features of the current vintage of econometric software and the progression of developments that has produced it are discussed next. Econometricians' tools and methods have changed over time, gradually evolving from an early emphasis on single and multiple equation linear models to the contemporary use of a huge variety of nonlinear techniques in addition to the traditional linear regression models. Software has evolved correspondingly, becoming more complex and flexible in the process. The common characteristics of software in econometrics are considered next. A natural progression has produced a broad similarity in both the look and feel and the capabilities of econometrics programs. As indicated earlier, the final sections of the article explore some of the interrelationships between econometric software and popular methods in econometrics.